Catalogue of multimorbidity mean based severity and associational prevalence rates between 199+ chronic conditions-A nationwide register-based population study. - Michael Falk Hvidberg; Anne Frølich; Sanne Lykke Lundstrøm; Nina Kamstrup-Larsen (PLoS ONE, 2022)
Background Real-world data on multimorbidity represents an important but underutilised source of evidence for the planning of healthcare services, including prevention, treatments, and health economic modelling. Aims This study aimed to estimate means of multimorbidity and provide associated prevalence rates and frequencies between 199 x 199 chronic conditions and disease groups based on the total adult Danish population and sex, age, and educational attainment. Thus, this study provides an off-the-shelf catalogue for use in treatments and planning by clinicians, decision-makers and researchers. Methods The study population contained all Danish residents above 16 years on 1 January 2013 (n = 4,555,439). The data was based on the linkage of six national registers covering hospital contacts, services in general practice, filled-in out-of-hospital prescriptions, and educational attainments. The health registers were used to identify the 199 chronic conditions based on the ICD-10 classification system. Results The mean number of chronic conditions (NCC) was 2.2. The mean increased with age, women had a higher mean than men, and there was a social gradient with the mean increasing with lower educational attainment. The mean NCC varied from 3.3-9.8 among all conditions. Across disease groups, the highest mean NCC were found within disease group N (chronic renal failure, mean = 8.8), D (in situ and benign neoplasms; mean = 6.5), K (diseases of the digestive system; mean = 5.7), and H (diseases of the eye and the ear; mean = 5.6). The highest mean NCC among the 29 common diseases was heart failure, ischemic heart diseases, angina pectoris, stroke, and dementia, with a mean above 6.5. Several prevalent conditions like hypertension, arthritis, chronic lower respiratory diseases, depression, type 2 diabetes, and overweight transcended other conditions regarding the associated prevalence rates. As one of the most frequent, hypertensive diseases were highly associated with arthritis (50.4%), depression (37.4%), type 2 diabetes (75.4%), cancers (49.7%), and being overweight (39.7%)-meaning that 50.4% of people with arthritis, 37.4% of people with depression and so on also had hypertensive diseases. The largest differences in means between individuals with no educational attainment and individuals with high educational attainment were found within disease groups J (diseases of the respiratory system, ratio = 1.8), Q (congenital malformations, deformations, and chromosomal abnormalities, ratio = 1.7), and B (viral hepatitis and human immunodeficiency virus disease, ratio = 1.7). Conclusions The current study provides a nationwide off-the-shelf catalogue of multimorbidity means and real-world associations estimates of 199+ chronic conditions for future clinical treatments and health care systems planning. The findings described are just one example of numerous results and underline that multimorbidity is highly prevalent in the adult Danish population and that it is a vital condition transcending all future medical treatment. The data offer essential information on the multimorbidity burden of disease in future differentiated treatments, healthcare planning, and economic, aetiological, and other research.